Structured and unstructured viva voce assessment: A double-blind, randomized, comparative evaluation of medical students - Imran, Mohammed; Doshi, Chintan; Kharadi, Darshan (International Journal of Health Sciences, 2019)
Objectives: The proper assessment orients learning in the desired direction. The structuring of assessment tools helps in minimizing the examination bias. However, the structuring of viva voce (SVV) has not been tried much. Therefore, this study was conducted to comparatively evaluate the structured written theory examination (STE) outcome with structured and unstructured viva voce assessments in third semester MBBS students. Methodology: Twenty uniform viva voce cards each containing eight structured questions with equitable, progressive cognitive levels were prepared. The random permutation (randomization) was done by shuffling the cards before the student picked up one card in a double-blind fashion. Of 135 students, 33–35 students per day were assessed for 4 continuous days through checklist-based evaluation by the same examiner following the STE. Parallel unstructured practical viva voce assessment was done for a major practical exercises held. Results: The intragroup percentage coefficient of variance values progressively increased in order of unstructured practical viva assessment (UPA%, 18.25) < structured written theory examination (STE%, 47.26) < structured theory viva voce (SVV%, 63.91). Thus, SVV% is more discriminatory than UPA%. The students in appropriate categories were 72 (53%) in%vSTE-SVV, 18(13%) in %vSTE-UPA, and 20 (14%) in %vSVV-UPA, respectively. A very high statistically significant correlation (P = 0.001) is seen between STE% and SVV% and highest erroneous results are seen in %vSVV-UPA (110, 81%). Conclusion: The SVV provides uniform, equitable, unbiased, and reflective assessment of students. Thus, a comprehensive objective and meaningful assessment can be achieved by structuring of written theory, practical, and viva voce.